Cost and efficacy comparison of five prostate biopsy modalities: a platform for integrating cost into novel-platform comparative research. Issue 4 (November 2018) - Altok, Muammer; Kim, Bumyang; Patel, Bina; Shih, Ya-Chen; Ward, John; McRae, Stephen; Chapin, Brian; Pisters, Louis; Pettaway, Curtis; Kim, Jeri; Demirel, Huseyin; Davis, John
Abstract Background The cornerstone of prostate cancer diagnosis remains the transrectal ultrasound-guided biopsy (TRUS-BX), which most frequently occurs in the office setting under local anesthesia. However, there are now other techniques of prostate biopsy aimed at improving outcomes such as patient comfort, significant cancer detection, and infectious complications. The purpose of the present study is to compare the cost and efficacy outcomes of five different approaches. Methods We compared the comprehensive costs of a random sample size of 20−30 cases from each of the following: (1) local anesthesia TRUS-BX (reference), (2) sedation TRUS-BX, (3) general anesthesia transperineal template biopsy (TP), (4) sedation MRI-TRUS fusion biopsy (FB), and (5) sedation in-bore MRI biopsy (IB-MRI). Cost categories included pre-procedure, anesthesia pharmacy and recovery, and the technical/professional costs from urology, radiology, and pathology services. For procedure outcomes, we compared the larger cohorts of TRUS-BX, TP, and FB in terms of indication, cancer yield, and downstream decision impact. Results Compared with standard TRUS-BX, the total costs of sedation TRUS-BX, TP, FB, and IB-MRI increased significantly ×1.9 (90%), ×2.5 (153%), ×2.5 (150%), and ×2.2 (125%), respectively (p  < 0.001). Although there was no statistical difference between the total costs of TP, FB, and IB-MRI, these costs were significantly higher than those of TRUS-BX under either local anesthesia or sedation (p  < 0.05). The cost of TRUS-BX under sedation was significantly higher than that of TRUS-BX under local anesthesia (p  < 0.001). Compared to TRUS-BX, more significant cancers were detected in FB (16% vs. 36%) and TP (16% vs. 34%) groups (p  < 0.001). Conclusions Compared with standard TRUS-BX, the additions of imaging, sedation anesthesia, and transperineal template increase costs significantly, and can be considered along with known improvements in accuracy and side effects. Ongoing efforts to combine imaging and transperineal biopsy, especially in an outpatient/local anesthesia setting may lead to a higher cost/benefit.